Type 1 diabetes mellitus: beyond the insulin therapy - Fodor, Adriana; Cozma, Angela (Medicine and Pharmacy Reports, 2011)
Type 1 diabetes mellitus (DM1) is an autoimmune disease that leads to the destruction of insulin-secreting pancreatic β cells. This usually leads to absolute insulin deficiency and requires insulin treatment for survival. In spite of remarkable progress made, like self-glucose monitoring, advances in insulin therapy (insulin analogs, insulin pumps) and higher standards of care, most people with diabetes continue to develop disabling complications. Currently, the only reliable option for establishing durable normoglycemia in patients with DM1 is whole pancreas transplantation. In spite of excellent results, pancreas transplantation has become the therapy of choice only for a selected group of patients with end-stage renal disease (simultaneous pancreas-kidney transplantation or pancreas after kidney transplantation). Islets transplantation, applied to the patients with labile DM1, cannot achieve insulin independence in majority of patients and suffers from lack of organ donors and life-long imunosupression. A major goal of current diabetes research is to generate an abundant source of autologous glucose-responsive insulin-secreting cells that can replace the destroyed β cells and avoid immune rejection.